2021
DOI: 10.1159/000518516
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Chest Imaging by LUS and CT in COVID-19 Inpatients: The ECOVID Multicenter Study

Abstract: <b><i>Background:</i></b> Point-of-care lung ultrasound (LUS) score is a semiquantitative score of lung damage severity. High-resolution computed tomography (HRCT) is the gold standard method to evaluate the severity of lung involvement from the novel coronavirus disease (COVID-19). Few studies have investigated the clinical significance of LUS and HRCT scores in patients with COVID-19. Therefore, the aim of this study was to evaluate the prognostic yield of LUS and of HRCT in COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
4
23
0
4
Order By: Relevance
“…Berce et al underline the importance of LUS as a useful method in a bacterial or viral outbreak or in epidemic times [ 30 ]. Lately, several studies have shown a significant role of LUS in the evaluation of COVID-19 pneumonia, not only regarding its accuracy in the detection of lesions, but also in evaluating the risk of death and complications development [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berce et al underline the importance of LUS as a useful method in a bacterial or viral outbreak or in epidemic times [ 30 ]. Lately, several studies have shown a significant role of LUS in the evaluation of COVID-19 pneumonia, not only regarding its accuracy in the detection of lesions, but also in evaluating the risk of death and complications development [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if CT images present the highest accuracy, CT should not always be recommended for all children with COVID due to its significant irradiation potential. Furthermore, recent studies demonstrated a strong correlation between LUS and CT scores, proving that an ultrasound score higher than 20 (using 12-area score) is associated with an increased risk of complications and death [ 8 , 9 ]. As COVID-19 has become a worldwide disease, in many hospitals, the availability of CT scans for many patients diagnosed with COVID-19 is not widespread.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive data on LUS artefacts in a number of conditions have been published, but the development of LUS scores has opened the door to objective evaluation. These studies show a correlation between LUS scores and inflammation [ 29 ], lung function in CF, and even mortality prognosis [ 43 ] in several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that some diagnostic tools, including the lung ultrasound (LUC) may present some usefulness in diagnosis, optimization of treatment, and risk stratification in COVID-19 patients [ 30 , 31 , 32 ]. Therefore, a multidimensional assessment of risk factors for an unfavorable outcome of COVID-19, including the data from imaging diagnostics, could constitute an interesting approach.…”
Section: Discussionmentioning
confidence: 99%